(untitled) (Journal of Asian Development Studies, 2014)
Teachers face multiple transition of life because of impact of modernization, advancement of technology in field of education and demands of fast changing society. The change brings within it not only occupational stress but also internal stress, effecting him physically and leads to inefficiency or disability in correct performance of his duty. Without good teachers the best system is bound to fail whereas with good teachers the worst system can be largely overcome. So, it is important not only to measure occupational stress and use of coping strategies by teachers but also to study its relation with feeling of wellbeing. For this a sample of eighty teachers in the age range on twenty five to forty five years was included in the study through purposive sampling technique from different Govt. Schools of Chandigarh. Occupational Stress Index, Coping Checklist and PGI-Wellbeing scales were used to measure the occupational stress, coping strategies and feeling of wellbeing among teachers. After analysis of data revel that teacher are high on role overload, role conflict, unreasonable group and political pressure, under-participation and poor peer relations in work related stress. On the other hand teacher use coping strategies like positive cognition, problem solving and distraction. Results of the coefficient of correlation indicate that role overload, unreasonable group and political pressure have negative significant correlation with feeling of wellbeing. Responsibility for persons is also negative significant correlation with avoidance coping strategies. Under-participation has significant positive correlation with negative cognition, problem solving, magical thinking, religious, help seeking and total scores of coping strategies. Powerless ness has positive and significant correlation with distraction, religious, help seeking and total scores of coping strategies. Low status has positive significant correlation with positive cognition and total scores of coping strategies. Total scores of coping strategies have positive significant correlation with feeling of wellbeing. Hence, the study is pioneer in nature that reflects the importance of studying the occupational stress in teachers and there use of coping strategies.